The Effect on Foreign Direct Investment of Membership in the European Union - Bruno, Randolph Luca; Campos, Nauro Ferreira; Estrin, Saul (Journal of common market studies, 2021)
This article explores the impact of EU membership on foreign direct investment (FDI). It analyses empirically how the effects of such deep integration differ from other forms and investigates what drives these effects. Using a structural gravity framework on annual bilateral FDI data for almost every country in the world from 1985 to 2018, we find EU membership leads to about 60 per cent higher FDI investment into the host economy from outside the EU, and around 50 per cent higher intra‐EU FDI. Moreover, we find that the effect of EU membership on FDI is larger than from membership of the North American Free Trade Agreement, the European Free Trade Association and the Southern Common Market, and that the single market is the cornerstone of this differential impact.